2011
DOI: 10.1590/s1413-86702011000600016
|View full text |Cite
|
Sign up to set email alerts
|

Klebsiella ESBL bacteremia-mortality and risk factors

Abstract: Background: Extended spectrum β-lactamase (ESBL)-producing bacteria have become recognized as a problem in South America. The aim of this study was to evaluate risk factors and mortality rate in bacteremia caused by ESBL-producing Klebsiella pneumoniae in a Brazilian hospital. Methods: A three-year retrospective cohort study with 104 cases of K. pneumoniae bacteremia (61 ESBL and 43 non-ESBL). Several clinical and laboratory variables were evaluated. The outcome of interest was 30-day mortality. The adequate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
3
5

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(47 citation statements)
references
References 13 publications
2
36
3
5
Order By: Relevance
“…The main risk factors for colonization by ESBL-producing isolates include invasive procedures such as use of a central venous line or arterial catheter, length of hospital stay (especially in ICUs), urinary catheter, mechanical ventilation, severity of disease, and previous exposure to antibiotics (4) (17) . The highest incidence of ESBL-producing bacteria was found in the wards, especially in the ICU/N.…”
Section: Ethical Considerationsmentioning
confidence: 99%
“…The main risk factors for colonization by ESBL-producing isolates include invasive procedures such as use of a central venous line or arterial catheter, length of hospital stay (especially in ICUs), urinary catheter, mechanical ventilation, severity of disease, and previous exposure to antibiotics (4) (17) . The highest incidence of ESBL-producing bacteria was found in the wards, especially in the ICU/N.…”
Section: Ethical Considerationsmentioning
confidence: 99%
“…Hal ini berbahaya karena dapat meningkatkan risiko terjadinya infeksi saluran kemih, pyelonephritis dan sepsis sehingga akan meningkatkan morbiditas serta mortalitas (Widodo, 2010;Peleg & Hooper, 2010;Purnomo, 2008). Meningkatnya mortalitas berkaitan dengan terapi antibiotik yang tidak tepat terhadap bakteri penghasil ESBL (Tuon et al, 2011 (Cockeril et al, 2010).…”
Section: P E N D a H U L U A Nunclassified
“…The first reported β-lactamases TEM-1/2 and SHV-1, described since 1960 from E. coli and Klebsiella pneumoniae were usually chromosomal. They are the most medically important species, often isolated from severe infections in hospitalized or ambulatory patients [25][26][27][28][29]. Klebsiella spp.…”
Section: Introductionmentioning
confidence: 99%
“…with variation from one continent to another. The global multi-center surveillance study Tigecycline Evaluation and Surveillance Trial (TEST) reported from 2004 to 2009 an overall prevalence of ESBL producing Klebsiella pneumoniae isolated from intensive care units (ICUs), ranging from 12.8% in North America to 26.6% in Europe, 33.8% in the Middle East, 35.6% in the Asia-Pacific region, 45.5% in Latin America an up to 54.9% in Africa [33]. In addition, Hoban et al reported a prevalence of ESBL of 8.8% and 38.9% in North America and Europe respectively with a predominance of CTX-M15 subgroup [34] on Klebsiella pneumoniae strains isolated from urinary tract infections.…”
Section: Introductionmentioning
confidence: 99%